RANCANG BANGUN ALAT PEMANAS AIR DAN KONSERVASI ENERGI PADA MESIN PENDINGIN AC 1PK - Gilang Akbar Sumarta; Bambang Supradono; Aris Kiswanto (PSTE UNIMUS, 2012)
Presidential Instruction recently about saving and energt efficiency, it is necessary that efforts should be made to support the program. In energy savings in the household sector can be done in various wavs from the smallest thing turning off lights that are not necessary to the utilization of waste heatfrom air conditioning to hot water purposes. Alternative technologies, the heat energy generated by the air conditioning unit is the potential energy that can be utilized to get hot water for free. Given theclimate in Indonesia is quite hot, many hospitals, hotels, residential upper middle or apartment is equipped with air-conditioning and heat generated in the cooling system is disposed into the environment. Infact. the heat energy can be used for heating water can be usedf or water bath or otherpurposes. It is necessary to develop a means of combined cooling and heating water. These devices are expected simultaneously to increase comfort and save energy.Keywords: Conservation of energy in refrigeration I pk